Cultural Determinants of Economic Decision-Making: A Behavioural Economics Perspective - Abbasi, Summera Maqbool; Hajj, Fadia Al (Journal of Cultural Analysis and Social Change, 2025)
This study examines how cultural orientations influence economic decision behaviour using a second-order structural model based on behavioural economics principles. Four cultural dimensions individualism–collectivism, power distance, masculinity–femininity, and uncertainty avoidance were conceptualised as first-order reflective constructs forming a higher-order cultural values variable. Economic decision behaviour was modelled as a multidimensional construct comprising financial decision style, risk perception, and trust in institutions. Primary data were collected from 333 professional respondents in Pakistan, and variance-based Structural Equation Modelling was applied using Smart-PLS. The measurement model confirmed strong reliability, convergent validity, and discriminant validity. Structural results showed that cultural values exert a substantial positive effect on economic decision behaviour, while cultural sub-dimensions significantly contribute to overall cultural framing. Economic decision behaviour strongly predicted financial decision style and risk perception and moderately influenced institutional trust. These findings reinforce the behavioural economics perspective that decision-making is culturally embedded rather than purely rational, offering theoretical and practical insights for financial institutions, behavioural analysts, and policymakers operating in culturally diverse environments.